Anti-mycobacterium tuberculosis and cytotoxicity activities of ruthenium(II)/Bipyridine/Diphosphine/Pyrimidine-2-thiolate complexes: The role of the non-coordinated n-atom - Lima, Benedicto A. V.; Corrêa, Rodrigo S.; Graminha, Angelica E.; Kuznetsov, Aleksey; Ellena, Javier; Pavan, Fernando R. [UNESP]; Leite, Clarice Q. F. [UNESP]; Batista, Alzir A. (Sociedade Brasileira de Quimica (SBQ), 2016)
The [Ru(Spym)(bipy)(P-P)]PF6, [Spym = pyrimidine-2-thiolate anion; P-P = 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane and 1,1'-bis(diphenylphosphino)ferrocene] complexes were synthesized and characterized by spectroscopic, electrochemical and elemental analysis, and by X-ray crystallography. The minimal inhibitory concentration (MIC) of the compounds against Mycobacterium tuberculosis and the complex concentration causing 50% tumor cell growth inhibition (IC50) against breast cancer cells, MDA-MB-231, were determined. All three compounds gave promising values in both tests. It is interesting to mention that all three complexes display MICs against Mycobacterium tuberculosis showing higher activity than cycloserine, a second line drug used in the treatment of the illness. The complexes interact weakly with the DNA.
Keywords: Cytotoxity; Diphosphine ligand; Pyrimidine-2-thiolate; Ruthenium complexes; Tuberculosis